Single Propeller Design of Flying Electric Vehicles - Syahyogi, Abbi Ewton; Susilo, Sugeng hadi (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
The development of passenger drone technology has opened up new opportunities in the air transportation industry, offering innovative and efficient mobility solutions. One of the key components in eVTOL vehicle design is the propeller, which functions to produce the thrust required for takeoff, hovering and flying. Efficient and optimal propeller design is very important to improve the performance and energy efficiency of these vehicles. The method used in this research includes computational fluid dynamics (CFD) simulation analysis to model the interaction between the propeller and air flow. The methodology used includes computational fluid dynamics (CFD) simulations to analyze the air flow and forces acting on the propeller, as well as prototype testing to validate the simulation results.